STRATEGI PEMASARAN PARIWISATA BERKELANJUTAN COMMUNITY-BASED TOURISM BERDASARKAN TOURISM AREA LIFE CYCLE (TALC) DI DESA WISATA TETEBATU, LOMBOK TIMUR - Andrinata, Andrinata; sukmawati, sukmawati (Universitas Nusa Cendana, 2024)
Tetebatu Village is a Tourism Village that practices sustainable tourism through the implementation of Community-Based Tourism. The establishment of a Community-Based Tourism Tourism Village can be assessed using the Tourism Area Life Cycle (TALC) theory. To enhance tourism development, a marketing plan aligned with the different stages of the TALC theory can be used. The objective of this study is to ascertain and evaluate the status of Tetebatu Tourism Village using the TALC theory, and thereafter devise a suitable marketing strategy aligned with the various phases of the TALC model. This research employs a descriptive qualitative methodology, specifically focusing on investigating the life cycle of Tetebatu Village. The research utilizes primary data and secondary data as the types of data. The findings indicated that Tetebatu Village is currently in the developmental stage, marked by the growing participation of various stakeholders, including both the local community and the government. Considering the location of Tetebatu Tourism Village in TALC, the recommended marketing approach would involve implementing programming and promotion strategies. Additional marketing methods include implementing cost leadership by delivering reasonable prices, differentiating the tourism items being sold, and targeting certain segments.